2017
DOI: 10.18632/oncotarget.23232
|View full text |Cite
|
Sign up to set email alerts
|

BAFF and APRIL expression as an autoimmune signature of membranous nephropathy

Abstract: BackgroundBased on the fact that B-cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) have a regulatory role in B cell biology, excessive levels of these cytokines can promote autoimmune pathogenesis. However, the expression and implication remain unresolved in cases of membranous nephropathy (MN).ResultsThe plasma BAFF levels of the primary MN patients were higher than those of healthy controls but lower than those of secondary MN patients, whereas the APRIL levels were similar between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Therefore, it is necessary to identify non-invasive biomarkers that can be easily obtained and reflect current renal inflammation [ 34 ]. Over the last two decades, many clinical studies have demonstrated the presence of molecules associated with B-cell activation in the serum [ 29 , [35] , [36] , [37] ] and kidney tissues [ 24 , 26 , 28 , 38 ] of active LN patients. One study demonstrated that serum BAFF level was lower in SLE patients with nephrotic-range proteinuria than in SLE patients with less severe proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is necessary to identify non-invasive biomarkers that can be easily obtained and reflect current renal inflammation [ 34 ]. Over the last two decades, many clinical studies have demonstrated the presence of molecules associated with B-cell activation in the serum [ 29 , [35] , [36] , [37] ] and kidney tissues [ 24 , 26 , 28 , 38 ] of active LN patients. One study demonstrated that serum BAFF level was lower in SLE patients with nephrotic-range proteinuria than in SLE patients with less severe proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary BAFF mRNA was detectable in only a minority of patients (28.57%), mainly of class III and IV, and showed no correlation with other parameters of lupus activity or renal function, consistent with previous studies [ 25 , 30 ]. In contrast, we found that BAFF was detectable by immunohistochemistry in the majority of 52 kidney biopsy samples from LN patients [ 26 ]. Furthermore, patients with class IV LN exhibited the highest glomerular BAFF expression, and expression was correlated with activity index (r ​= ​0.4647, p ​= ​0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAFF is produced by the activation of radiation-resistant stromal cells, B cells, activated T cells, and most myelogenous cell lines, including monocytes, macrophage, and stimulated neutrophils, TLR9-activated plasmacytoid dendritic cells (DCs) and IL2-activated natural killer cells (Craxton et al, 2003;Gorelik et al, 2003;Krumbholz et al, 2005;Nardelli et al, 2001;Scapini et al, 2003;Vincent et al, 2012). Groom et al, 2002;Han et al, 2018;Hegazy et al, 2010;Kamhieh-Milz et al, 2018;Li et al, 2014;Vosters et al, 2012;Xin et al, 2013). Research shows that BAFF and APRIL are also associated with increased tumor growth and invasion in certain solid tumors such as breast cancer (Pelekanou et al, 2017).…”
Section: Baff and April In The Immune Systemmentioning
confidence: 99%
“…BAFF and APRIL can maintain the activation of B cells, enhancing autoimmune diseases. Overexpression of BAFF leads to the development of polyclonal B cell, hyperglobulinemia and autoimmunity diseases such as systemic lupus erythematosus (SLE), IgA nephropathy, membranous nephropathy, SS, immune thrombocytopenic purpura, and RA (Elbirt et al, ; J. Groom et al, ; Han et al, ; Hegazy et al, ; Kamhieh‐Milz et al, ; Li et al, ; Vosters et al, ; Xin et al, ). Research shows that BAFF and APRIL are also associated with increased tumor growth and invasion in certain solid tumors such as breast cancer (Pelekanou et al, ).…”
Section: Baff and April In The Immune Systemmentioning
confidence: 99%